Neuroimaging changes in brain structure during continuous pressure device treatment in patients diagnosed with obstructive sleep apnea : a systematic review (2020)
What are the neuroimaging changes in obstructive sleep apnea patients who have been treated with continuous positive airway pressure device compared to those who have not been treated? This review will include randomised control triales (RTC), controlled clinical trials (CCT), observational analytical studies such a cohort studies. Studies will be considered only if they have observed and evaluated changes in structural and functional brain MRI neuroimaging in people with OSA receiving CPAP.